2016
DOI: 10.1002/ijc.30253
|View full text |Cite
|
Sign up to set email alerts
|

Leiodermatolide, a novel marine natural product, has potent cytotoxic and antimitotic activity against cancer cells, appears to affect microtubule dynamics, and exhibits antitumor activity

Abstract: Pancreatic cancer, the fourth leading cause of cancer death in the United States, has a negative prognosis because metastasis occurs before symptoms manifest. Leiodermatolide, a polyketide macrolide with antimitotic activity isolated from a deep water sponge of the genus Leiodermatium, exhibits potent and selective cytotoxicity towards the pancreatic cancer cell lines AsPC-1, PANC-1, BxPC-3, and MIA PaCa-2, and potent cytotoxicity against skin, breast and colon cancer cell lines. Induction of apoptosis by leio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
24
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 30 publications
(75 reference statements)
0
24
0
Order By: Relevance
“…Inevitably, NMR analysis takes the minority of the time and reveals the majority of the structural information, but relies on synthetic efforts to fill in the gaps. Going forward, the development of a practical total synthesis of leiodermatolide should enable access to both a sustainable supply and designed analogs for further evaluation of this promising new experimental antimitotic drug in cancer chemotherapy ,…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Inevitably, NMR analysis takes the minority of the time and reveals the majority of the structural information, but relies on synthetic efforts to fill in the gaps. Going forward, the development of a practical total synthesis of leiodermatolide should enable access to both a sustainable supply and designed analogs for further evaluation of this promising new experimental antimitotic drug in cancer chemotherapy ,…”
Section: Discussionmentioning
confidence: 99%
“…It was also suggested that leiodermatolide could be acting as a centrosome‐declustering agent, but this hypothesis requires verification. Preliminary evaluation in vivo in a mouse model of metastatic pancreatic cancer led to a significant reduction in tumour size, underscoring leiodermatolide's clinical potential as a new experimental chemotherapeutic lead for pancreatic and other solid tumours …”
Section: Introductionmentioning
confidence: 99%
“…Despite advanced BC treatment modalities are available, advanced stage of BC patients, develop resistant to current therapeutic options. Chemotherapy resistance leads into cancer progression and metastasis, thereby it remains as the greatest challenges in cancer management compound demonstrates a powerful anti-tumor activity compared to paclitaxel in prostate cancer cells (Guzmán et al, 2016). Above data indicating that sponges are very potential to be studied for novel anti-cancer drug discovery.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the provision of Ecosystem Services has been argued as one standard for assessing "serious harm" in the context of DSM Environmental Impact Assessments (EIAs) (Le et al, 2017), because these services link environmental health to human wellbeing. Provisioning Services include supporting fisheries for human nutrition (e.g., Gordon, 2001) and novel natural products (e.g., Guzman et al, 2016), whilst Regulating Services include the absorption of carbon from the atmosphere and its subsequent sequestration with the deep ocean interior and within the seabed (e.g., Vardaro et al, 2009). At the sea floor diverse and stable biological communities represent a biodiversity resource which provides a reservoir of biological and genetic resources that might present the source of future natural products of further benefit to human kind (Harden-Davies, 2017).…”
Section: Introductionmentioning
confidence: 99%